Sequencing and Analysis of the Myostatin Gene (GDF-8) in Bubalus bubalis Young Animals to Determine the Existence of Possible Mutations Expressed in Double Musculature Phenotype - Páez, María Angélica Reyes; Tovar, Natalia Johana Rojas; MendozaSánchez, Geovanny; Muñoz, Marcela Fernández; Molina, Boris Julián Sepúlveda; Torres, Andrés Felipe Santander; Gutíerrez, Jesús Alfredo Berdugo; Buitrago, Jhon Didier Ruiz (Journal of Buffalo Science, 2021)
Since the 19th century, the presentation of bovines with disproportionate muscle development have been associated with mutations that inhibit the action of the myostatin gene, it is referred to as double muscle mutation, which is common in some European Bos taurus breeds but it is not reported in buffaloes Bubalus bubalis. This study aims to evaluate if the phenotype observed in 6 young buffaloes with disproportionate muscle development has the same myostatin mutation reported in cattle. DNA was obtained from the blood of the animals of the Murrah breed. First, second and third exon was amplified end point PCR; the fragments were sequenced using capillary electrophoresis. Holstein cattle (Bos taurus) was used As control for normal phenotype. The results obtained from the comparison of the sequence of the myostatin gene show that the observed double-muscled phenotype did not show differences from normal controls. Interspecific variation was demonstrated by comparing exons two and three of the gene, finding 12 variations between the Bos taurus and Bubalus bubalis species in the evaluated fragments. It is necessary to study physiology, and the animals to explain the phenotype observed in buffaloes.